Design and Implementation of a Solar Panel Inverter as STATCOM Compensator - Alnahhas, Mutaz; Abdul Ali, Abdul Wali (ELEKTRIKA- Journal of Electrical Engineering, 2021)
A power system suffers from different losses, which can cause tragic consequences. Reactive power presence in the power system increases system losses delivered power quality and distorts the voltage. As a result, many researches are concerned with reactive power compensation. Moreover, reactive power should not be transmitted through a transmission line to a longer distance. Thus, Flexible AC Transmission Systems (FACTS) devices such as static synchronous compensator (STATCOM), static volt-ampere compensator (SVC), and unified power flow controller (UPFC) are utilized to overcome these issues. The necessity of balancing resistive power generation and absorption throughout a power system becomes a big concern in the electrical systems for reactive power compensation. Static synchronous compensator STATCOM is a shunt device used for the generation or absorption of reactive power as desired. STATCOM provides smooth and fast compensation and power factor correction. In this thesis, a solar Static synchronous compensator takes the DC input from the solar panel and inverted utilizing an H-bridge inverter. This topology is used for reactive power compensation and power factor correction at the load side. The simulation was done using MATLAB Simulink simulation tools. The system model was built using a single solar array for DC input and controlled using perturbation and observe method to maximize its power output. The STATCOM model was built using for high power MOSFETs to perform H- bridge inverter. The STATCOM was controlled using a hysteresis band current control using a PI controller to inject the current into the system. A hardware prototype of STATCOM was built and controlled using an Arduino microcontroller. The simulation results have demonstrated the STATCOM model of reactive power compensation and correcting the power factor under different loads of conditions. It also highlighted the proportional relation between reactive power presence and the increased cost of electricity bills. The proposed smart meter of STATCOM gives accurate reading and measurement. Overall, the simulated results showed a satisfactory level of compensation of reactive power and power factor correction. The system contained three significant parts; solar array, H- bridge inverter, and the PI controller. The smart meter circuit was capable of displaying readings regarding input solar voltage, current, and power factor on the LCD screen.